Integration and insertion of freshmen in Physical Education in a Federal Institution of Higher Education: Experiences of the 2020 Freshmen Reception Week 2020 (Research, Society and Development, 2021)
The manuscript aims to report and describe the “Freshman Reception Week” of a Physical Education course. Specifically, it seeks to present the actions developed and the results achieved. This is a described study, of the experience report type, of an action organized by the Tutorial Education Program at the Federal University of Mato Grosso do Sul, in 2020. Carried out in five days, students (newcomers and veterans), teachers and civil servants participated. administrative. Provided the reception (welcome, explanation of the “Trote Solidarity – Collection of food and clothes”, presentation of the schedule and spaces of the institution); academic-scientific-pedagogical lecture on the training of graduates and bachelors and the field of professional activity; presentation of the coordinator, teachers, administrative staff, institutional programs linked to the course - Tutorial Education Program, Teaching Initiation Program, Scientific Initiation Program, Second Term University Program -, projects, study groups and student representative entities (Academic Center of Physical Education and Academic Athletic Association of Physical Education) and recreational/sporting activities (Futsal Tournament, Gymkhana and sports), which counted with the participation of 29 (2/17), 34 (2/18 and 2/20) and 19 (2/21) freshmen and 41 (2/17), 27 (2/18), 7 (2/20) and 16 (2/21) veterans. It is concluded that the proposal promoted the reception of newcomers in a respectful and informative manner and integrated them with veterans, teachers and administrative staff, as well as promoting informational access to types of training and professional performance, projects, programs, representative entities and possible experiences of enjoy at Cidade Universitária, although adjustments to future editions are necessary.